Diffusion-weighted MRI-Derived ADC and tumor volume as predictive imaging markers for neoadjuvant chemotherapy response in muscle-invasive bladder cancer - Abolfazl Razzaghdoust; Anya Jafari; Arash Mahdavi; Bahram Mofid; Abbas Basiri (BMC Medical Imaging)
Abstract Background This prospective study tested the hypothesis that the apparent diffusion coefficient (ADC) value and tumor volume (TV) measured in diffusion-weighted magnetic resonance imaging (DW-MRI) before, during, and after the treatment are quantitative imaging markers to assess tumor response in muscle-invasive bladder cancer (MIBC) patients undergoing neoadjuvant chemotherapy (NAC). Methods Multi-parametric MRI was prospectively done for MIBC patients at 3 time points. Pre-treatment ADC value, pre-treatment TV, as well as, percent of changes (ΔADC%, and ΔTV%) in these parameters at mid- and post-treatment relative to baseline were calculated and compared between the patients with and without clinical complete response (CR). Also, further analysis was carried out based on the groups of patients with and without overall response (OR). Two different methods of ADC estimation including single-slice ADC measurement (ADCsingle-slice) and whole-lesion ADC measurement (ADCwhole-lesion) were used. Results A total of 50 eligible patients were included in the analysis. Of these, 20 patients (40%) showed clinical CR to treatment, while 30 (60%) did not. Our results showed that although there was no significant difference between the two groups of patients with and without CR in terms of mid-treatment ΔADC% and mid-treatment ΔTV%, significant differences were observed in terms of the pre-treatment ADC (p < 0.01), pre-treatment TV (p < 0.001), post-treatment ΔADC% (p < 0.05), and post-treatment ΔTV% (p < 0.05). The results of the OR-based analysis were in line with the CR-based results. There was also a strong and significant correlation between ADCsingle-slice and ADCwhole-lesion measurements (r > 0.9, P < 0.001). Conclusion Pre-treatment ADC, pre-treatment TV, post-treatment ΔADC%, and post-treatment ΔTV% could be considered as promising quantitative imaging markers of tumor response in MIBC patients undergoing NAC. Moreover, mid-treatment ΔADC% and mid-treatment ΔTV% should not be used as predictors of tumor response in these patients. Further larger studies are required to confirm these results.